MODERN APPROACH TO TREATMENT OF ACUTE OTITIS MEDIA IN CHILDREN - E. P. Karpova; L. I. Usenya (Вопросы современной педиатрии, 2012)
The problem of acute otitis media in children is discussed in this article. The author describes etiology, pathogenesis and methods of diagnostic of this disease. The article contains information about clinical efficacy and good tolerance of the drug “Otofa” in treatment of acute otitis media in children. The usage of this topic antibacterial agent in complex treatment of acute otitis media is safe in point of systemic side effects and undesirable medicinal interactions, which allows to achieve perfect result and improve life quality of children with inflammatory diseases of middle ear.